Determination of the loss of function complement C4 exon 29 CT insertion using a novel paralog-specific assay in healthy UK and Spanish populations. - Lora Boteva; IMAGEN; Yee Ling Wu; Josefina Cortes-Hernández; Javier Martin; Timothy J Vyse; Michelle M A Fernando (PLoS ONE)
Genetic variants resulting in non-expression of complement C4A and C4B genes are common in healthy European populations and have shown association with a number of diseases, most notably the autoimmune disease, systemic lupus erythematosus. The most frequent cause of a C4 "null" allele, following that of C4 gene copy number variation (CNV), is a non-sense mutation arising from a 2 bp CT insertion into codon 1232 of exon 29. Previous attempts to accurately genotype this polymorphism have not been amenable to high-throughput typing, and have been confounded by failure to account for CNV at this locus, as well as by inability to distinguish between paralogs. We have developed a novel, high-throughput, paralog-specific assay to detect the presence and copy number of this polymorphism. We have genotyped healthy cohorts from the United Kingdom (UK) and Spain. Overall, 30/719 (4.17%) individuals from the UK cohort and 8/449 (1.78%) individuals from the Spanish cohort harboured the CT insertion in a C4A gene. A single Spanish individual possessed a C4B CT insertion. There is weak correlation between the C4 CT insertion and flanking MHC polymorphism. Therefore it is important to note that, as with C4 gene CNV, disease-association due to this variant will be missed by current SNP-based genome-wide association strategies.